Cosmic transparency and acceleration - Holanda, R. F.L.; Pereira, S. H. [UNESP]; Jain, Deepak (American Physical Society (APS), 2018)
In this paper, by considering an absorption probability independent of photon wavelength, we show that current type Ia supernovae (SNe Ia) and gamma-ray burst (GRB) observations plus high-redshift measurements of the cosmic microwave background (CMB) radiation temperature support cosmic acceleration regardless of the transparent-universe assumption. Two flat scenarios are considered in our analyses: The ΛCDM model and a kinematic model. We consider τ(z)=2ln(1+z)Ïμ, where τ(z) denotes the opacity between an observer at z=0 and a source at z. This choice is equivalent to deforming the cosmic distance duality relation as DLDA-1=(1+z)2+Ïμ and, if the absorption probability is independent of photon wavelength, the CMB temperature evolution law is TCMB(z)=T0(1+z)1+2Ïμ/3. By marginalizing on the Ïμ parameter, our analyses rule out a decelerating universe at 99.99% C.L. for all scenarios considered. Interestingly, by considering only SNe Ia and GRBs observations, we obtain that a decelerated universe-indicated by ΩΛ≤0.33 and q0>0-is ruled out around 1.5σ C.L. and 2σ C.L., respectively, regardless of the transparent-universe assumption.